Genesis, John H. Walton : book review - Ramantswana, Hulisani (Old Testament essays, 2013)
This commentary was previously also a part of the Zondervan Illustrated Bible Backgrounds Commentary, Volume 1, Genesis, Exodus, Leviticus, Numbers, Deuteronomy, published in 2009, of which Walton was the general editor. The Zondervan Illustrated Bible Backgrounds Commentary also includes Volume 2 (Joshua, Judges, 1 and 2 Samuel), Volume 3 (1 and 2 Kings, 1 and 2 Chronicles, Ezra, Nehemiah, Esther), and Volume 4 (Isaiah, Jeremiah, Lamentations, Ezekiel, Daniel). Monetarily, Volume 1 is selling at a reasonable price compared to buying a single book commentary. If one is simply interested in Genesis, buying the single book commentary is the way to go; however, to get the best value for money, the volumes are a better deal.